2018
DOI: 10.3390/genes9090455
|View full text |Cite
|
Sign up to set email alerts
|

Correction of a Splicing Mutation Affecting an Unverricht-Lundborg Disease Patient by Antisense Therapy

Abstract: Unverricht-Lundborg disease (ULD) is a common form of progressive myoclonic epilepsy caused by mutations in the cystatin B gene (CSTB) that encodes an inhibitor of several lysosomal cathepsins. Presently, only pharmacological treatment and psychosocial support are available for ULD patients. To overcome the pathogenic effect of the ULD splicing mutation c.66G>A (exon 1), we investigated whether an antisense oligonucleotide therapeutic strategy could correct the defect in patient cells. A specific locked nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
12
0
2
Order By: Relevance
“…This adds evidence to the feasibility of ASO therapies and highlights the importance of personalised treatment of ULD patients (Ref. 54). As one of the pathological determinants of ULD is the presence of oxidative stress (see above), some reports have recently indicated that ULD patients treated with high doses of N-acetyl-cysteine showed marked improvement in seizures, ataxia and blockade of symptoms progression (reviewed in Ref.…”
Section: Similarities and Dissimilarities In The Neuroinflammatory Rementioning
confidence: 86%
“…This adds evidence to the feasibility of ASO therapies and highlights the importance of personalised treatment of ULD patients (Ref. 54). As one of the pathological determinants of ULD is the presence of oxidative stress (see above), some reports have recently indicated that ULD patients treated with high doses of N-acetyl-cysteine showed marked improvement in seizures, ataxia and blockade of symptoms progression (reviewed in Ref.…”
Section: Similarities and Dissimilarities In The Neuroinflammatory Rementioning
confidence: 86%
“…As expected, patient's treated fibroblast expressed only the normal spliced transcript, with normal CSTB protein levels. Moreover, the recovery was LNA dose-specific, without evidences of increased cell death [75].…”
Section: Antisense Oligonucleotides (Asos) Therapiesmentioning
confidence: 89%
“…Hence, the use of ASOs in clinical practice requires overcoming problems related to the design, bioavailability, and targeted delivery ( 78 ). To date, few in-human studies have been conducted that primarily addressed invariably progressive and fatal diseases such as PMEs ( 79 , 80 ). The authors proved the feasibility of the ASOs-based approach by specifically customizing oligonucleotides over the genetic defect of patients.…”
Section: Gene Therapiesmentioning
confidence: 99%